An Analytical Background Study of Urdu Poem: Similarities and Divergences - Dr. Nabeel Ahmad Nabeel; Dr. Sher Ali; Dr. Imran Zafar (Zaban-o-Adab, 2023)
In this article, how Urdu 'Nazm' has traversed, transformed and enriched itself both as a literary genre and a vehicle of enunciation of newer and unique ideas has been elaborated upon. Individuality of Urdu poets can be traced to different sources and can be discussed from different perspectives, which includes both a departure from established tradition and a certain bond with the same tradition. It includes individual way of expression (s) as well as poet's individuality per se. In Urdu poem, we find the first voice of dissent from the beaten track in the form of different poetry of Nazir Akbar Abadi who for the first time gave representation to ' People’, their interests, their life lived as ordinary individuals. Thus,Nazir's contribution towards replenishment of Urdu poetry in general and the genre ' Nazm' in particular, is immense. The next stage in this splendid voyage of Urdu Nazm and its evolution is definitely Allama Iqbal who not only invoked the message of Muslim Renaissance, but also replenished and invigorated Urdu Nazm in terms of vitality of language and dexterity of purpose. After Iqbal, came a plethora of poets like Rashid, Meeraji, MajeedAmjad, Faiz who were not only distilled in local literary tradition, but had a deep understanding of modern world, it's sensibilities and modern Western literature. In this particular effort which is before your kind readership, an effort has been made to imbibe all the three stages of the journey of Urdu poem with a fresher perspective.